Pendidikan Kesehatan dengan Media E-Buklet Terhadap Pengetahuan dan Sikap SADARI (Pemeriksaan Payudara Sendiri) - Vika Riris Dwi Purwanti; Sri Sumarni; Intan Nugraheni Hasanah (Midwifery Care Journal, 2026)
In Indonesia, the prevalence of breast cancer has surpassed 22 thousand documented cases. Central Java Province exhibits the highest incidence rate of breast cancer in Indonesia, recorded at 0.7%. A primary strategy for breast cancer control involves the dissemination of health education aimed at enhancing the knowledge and attitudes regarding Breast Self-Examination (BSE) among adolescent females. The objective of this study is to assess the impact of health education utilizing e-booklet media on the knowledge and attitudes related to BSE among adolescent girls. This investigation employed a Pre-Experimental design featuring a two-group pretest and posttest with a control group framework. The sample was derived using a total sampling methodology, resulting in 61 respondents. Data analysis was conducted using the Wilcoxon test and the Mann Whitney test. The findings of the study indicated that health education incorporating e-booklet media significantly influenced knowledge and attitudes prior to and following the intervention, as evidenced by the Wilcoxon test results, which yielded a p-value of 0.000 for knowledge and a p-value of 0.000 for attitude. Additionally, a notable difference in impact between the two groups was identified, as indicated by the Mann Whitney test, which reported a p-value of 0.004 for knowledge and a p-value of 0.009 for attitude. There exists a significant influence of health education with e-booklet media on the enhancement of knowledge and attitudes concerning BSE (Breast Self-Examination). It is anticipated that adolescents will engage in BSE practices accurately and consistently, thereby facilitating early detection of breast cancer.